The Coherent X‐ray Imaging instrument at the Linac Coherent Light Source. (14th April 2015) - Liang, Mengning; Williams, Garth J.; Messerschmidt, Marc; Seibert, M. Marvin; Montanez, Paul A.; Hayes, Matt; Milathianaki, Despina; Aquila, Andrew; Hunter, Mark S.; Koglin, Jason E.; Schafer, Donald W.; Guillet, Serge; et al.
<x xml:space="preserve">Abstract</x> The Coherent X‐ray Imaging (CXI) instrument specializes in hard X‐ray, in‐vacuum, high power density experiments in all areas of science. Two main sample chambers, one containing a 100 nm focus and one a 1 µm focus, are available, each with multiple diagnostics, sample injection, pump–probe and detector capabilities. The flexibility of CXI has enabled it to host a diverse range of experiments, from biological to extreme matter.